Haematology and Serum Biochemistry Characteristics of Broiler Chicks Fed Varying Dietary Levels of Ipomoea asarifolia Leaf Meal - Madubuike, F.N.; Ekenyem, B.U. (International Journal of Poultry Science, 2005)
A 49-day feeding trial involving 240 one-week old Anak broiler chicks was carried out to study the haematology and serum biochemistry of broilers fed varying dietary inclusion levels of Ipomoea asarifolia leaf meal. The birds were grouped into four dietary treatments of 0%, 5%, 10% and 15% levels of Ipomoea asarifolia leaf meal (IALM), which were further replicated 4 times in a completely randomized design. Feed and water supply were offered to birds ad libitum while standard management practices were meticulously adopted. At the 8th week of age, 16 birds were randomly selected (4 per treatment), bled 9.00am - 10.00am from punctured vein to aspirate 7mls of blood from each bird for haematology and serum assay. Results of the haematology parameters showed significant differences (P< 0.05) between treatments, indicating that IALM influenced the values of the parameters. However, packed cell volume (PCV) and Eosinophil did not significantly differ (P>0.05) between their treatments. This shows that the IALM influenced the serum chemistry of Anak broilers as their values reduced with increasing levels of IALM.